Malignant thyroid pathology. Callao, Sabogal Hospital - Oré, Juan (2004)
OBJECTIVES: To determine the clinical characteristics of thyroid cancer at Callao’s population. DESIGN: Descriptive and retrospective study. MATERIAL AND METHODS: Clinical histories and surgical reports that involved the thyroid gland were reviewed. The pathology result had to be compatible with primary thyroid malignant neoplasm. The study was performed at the Alberto Sabogal Sologuren National Hospital (HNASS) during the period January 2000 through December 2002. RESULTS: Forty-five thyroid malignant neoplasms were identified representing 34,2% of all thyroid neoplasms operated during the period studied. In males papillary carcinoma was present in 100% of cases and in females in 82,1%, followed by both follicular and medullar carcinoma and lymphoma, in 10,2%, 5,1% and 2,6%, respectively. Major incidence was in the 50 to 69 years group, average 53 years. The most frequent malignant neoplasms were papillary carcinoma with 38 cases (84,4%), follicular and medullary carcinoma with 8,9% and 4,4%, respectively. Most frequent symptoms were growing tumor (61,5%), local pain (15,4%), dysphagia (10,8%) and dysphonia (9,2%); 29,6% of cases were on stage I, 59,1% on stage II, and only 11,4% on stage III. CONCLUSIONS: Papillary carcinoma occurred mainly in women and clinical features were as described in the literature.